Accuracy of References in Different Speciality Medical Journals of Nepal - Adhikari, P; Acharya, R (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Keywords: References; accuracy; speciality medical journals DOI: 10.3126/njenthns.v1i2.4762 Nepalese J ENT Head Neck Surg Vol.1 No.2 (2010) p.23-25